Strategies preventing contrast-induced nephropathy after coronary angiography: a comprehensive meta-analysis and systematic review of 125 randomized controlled trials - Ali-Hasan-Al-Saegh, Sadeq; Weymann, Alexander (Angiology, 2017)
This systematic review with meta-analysis sought to determine the strength of evidence for the effects of hydration (sodium bicarbonate [SB] and normal saline [NS]), supplementations ( N-acetylcysteine [NAC] and vitamin C), and some common drugs (adenosine antagonists [AAs], statins, loop diuretics, and angiotensin-converting enzyme inhibitors [ACEIs]) on the incidence of contrast-induced nephropathy (CIN) and requirement for hemodialysis after coronary angiography. After screening, a total of 125 trials that reported outcomes were identified. Pooled analysis indicated beneficial effects of SB versus NS (odds ratio [OR] = 0.73; 95% confidence interval [CI]: 0.56-0.94; P = .01), NAC (OR = 0.79; 95% CI: 0.70-0.88; P = .001), vitamin C (OR = 0.64; 95% CI: 0.45-0.89; P = .01), statins (OR = 0.45; 95% CI: 0.35-0.57; P = .001), AA (OR = 0.28; 95% CI: 0.14-0.47; P = .001), loop diuretics (OR = 0.97; 95% CI: 0.33-2.85; P = .9), and ACEI (OR = 1.06; 95% CI: 0.69-1.61; P = .8). Overall, hydration with SB, use of supplements, such as NAC and vitamin C, and administration of statins and AA should always be considered for the prevention of CIN after coronary angiography.
Published online: August 1, 2016
Gesehen am 25.04.2018